Microstructure, interfacial reaction and shearing property of Sn-58Bi solder joints reinforced by Zn particles during isothermal aging - Yao, Xin; Tian, Shuang; Zhou, Minhao; Jiao, Honghao; Wang, Jianfeng; Wang, Bo (Frontiers in Materials, 2025)
In this paper, micro-sized Zn particles were added into Sn-58Bi solder flux to form Sn-58Bi-xZn composite solder. The evolution of microstructure, interfacial IMCs and shearing properties during long-term aging were investigated. The wettability of Sn-58Bi-xZn solder decreased with the increase in Zn content. Adding the Zn element refined the microstructure of Sn-58Bi solder and mitigated the aggregation of Bi phases during aging. The interfacial IMCs changed from Cu6Sn5 to Cu6(Sn,Zn)5 with 0.5 wt% Zn addition. Further increasing the Zn content, Cu5Zn8 instead of Cu6(Sn,Zn)5 generated at the Sn-58Bi-2.0Zn/Cu interface. After long-term aging, Bi diffused into Cu3Sn and formed an aggregation layer. With 0.5 wt% Zn addition the growth of interfacial Cu6Sn5 IMCs was suppressed. Shearing tests were conducted to evaluate the mechanical properties of Sn-58Bi-xZn joints before and after aging. Aging and excess Zn addition lead to a decrease in the shearing force of the joints. The fracture mode changed from solder fracture to interface fracture with excess Zn addition The Sn-58Bi-0.5Zn solder joints exhibited the optimal shearing properties during aging. The optimum amount of Zn addition to Sn-58Bi solder was 0.5 wt%.